2019
DOI: 10.1111/gfs.12419
|View full text |Cite
|
Sign up to set email alerts
|

Impact of field fungal contamination of barley on ensiling properties, nutritional quality and the microbiome of barley silage

Abstract: Barley varieties of differing fungal disease resistance were grown in triplicate plots at Lacombe and Lethbridge, Alberta with the disease resistant variety (FR) sprayed with a foliar fungicide to maximize differences in field fungal disease. Both varieties were harvested at soft dough and ensiled in minisilos to assess differences in fungal contamination on ensiling properties, nutritional quality, aerobic stability and associated bacterial and fungal microbiomes. Data were analysed as repeated measures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…However, others detected no effect of dual-purpose inoculants containing Lactobacillus buchneri and homofermentative species on DM losses in whole-crop barley silage [12,48], whereas Romero et al [49] reported reduced losses in whole-crop oat silage, substantiating our results on WCR silage. The observed differences between studies regarding the additive effect on DM losses may be explained by differences in DM affecting the fermentation intensity [13], by different storage length and conditions (strict anaerobic storage vs. storage with repeated air ingress), and by variation in the epiphytic bacterial and fungal microbiome between cereal species [50], and even between varieties within species [51]. It is worthwhile mentioning here that, based on the assessment of a selected contrast (p < 0.01) comparing the Lactobacillus buchneri-containing inoculants LAB he and LAB heho (mean DM loss: 5.1%) with the chemical additives NHS and BSP (mean DM loss: 4.0%), our data confirm previous observations on a consistently larger magnitude of the effect by chemical additives [18,19].…”
Section: Dry Matter Losses and Fermentation Characteristicsmentioning
confidence: 99%
“…However, others detected no effect of dual-purpose inoculants containing Lactobacillus buchneri and homofermentative species on DM losses in whole-crop barley silage [12,48], whereas Romero et al [49] reported reduced losses in whole-crop oat silage, substantiating our results on WCR silage. The observed differences between studies regarding the additive effect on DM losses may be explained by differences in DM affecting the fermentation intensity [13], by different storage length and conditions (strict anaerobic storage vs. storage with repeated air ingress), and by variation in the epiphytic bacterial and fungal microbiome between cereal species [50], and even between varieties within species [51]. It is worthwhile mentioning here that, based on the assessment of a selected contrast (p < 0.01) comparing the Lactobacillus buchneri-containing inoculants LAB he and LAB heho (mean DM loss: 5.1%) with the chemical additives NHS and BSP (mean DM loss: 4.0%), our data confirm previous observations on a consistently larger magnitude of the effect by chemical additives [18,19].…”
Section: Dry Matter Losses and Fermentation Characteristicsmentioning
confidence: 99%
“…(2022) , who reported that after 12 days of aerobic exposure, the richness and diversity of fungal community decreased in whole-crop wheat silage. Meanwhile, the richness of the fungal community also decreased in barley silage ( Nair et al., 2019 ). The reason for this might be that the proliferation of acetic acid bacteria on aerobic exposure, which has an inhibitory effect on fungi ( Driehuis and Van Wikselaar, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…This response was likely due to lower residual WSC and the higher concentration of AC in INOC inhibiting the growth of yeast. The composition of terminal silage has a major impact on the aerobic stability of silages (Nair et al, 2019a). Greater amounts of residual WSC can serve as a substrate for spoilage microorganisms during AE (Addah et al, 2012).…”
Section: Effects Of Inoculant On the Aerobic Stability Of Whole-crop Corn Silagementioning
confidence: 99%